The Response of the miRNA Profiles of the Thyroid Gland to the Artificial Photoperiod in Ovariectomized and Estradiol-Treated Ewes - Zizhen Ren; Wei Wang; Xiaoyun He; Mingxing Chu (Animals)
The photoperiod has been considered to be a key environmental factor in sheep reproduction, and some studies have shown that the thyroid gland plays an important role in mammalian reproduction, but the molecular mechanism is still unclear. In this study, we used the artificial-light-controlled, ovariectomized, and estradiol-treated model (OVX + E2 model); healthy and consistent 2–3-year-old Sunite multiparous ewes were collected; and thyroids were collected for testing, combined with RNA-seq technology and bioinformatics analysis, to analyze the effects of different photoperiods (long photoperiod treatment for 42 days, LP42; short photoperiod treatment for 42 days, SP42; SP42 transferred to LP42, SPLP42) on the variations in the miRNA profiles of the thyroid gland. A total of 105 miRNAs were differentially expressed in the thyroid gland, most of which were new miRNAs. Through GO and KEGG enrichment analysis, the results showed that the photoperiod response characteristics of Sunite ewes were affected by Olfactory transduction, Wnt signaling pathways, and Apelin signaling pathways. A different illumination time may have a certain influence on the downstream of these pathways, which leads to the change in animal estrus state. In addition, lncRNA-mRNA-miRNA network analysis revealed the target binding sites of identified miRNAs in DE-circRNA and DE-mRNA, such as Novel_369, Novel_370, Novel_461, and so on. The results of this study will provide some new insights into the function of miRNA and the changes in sheep thyroid glands under different photoperiods.